The Relationship Between Belief System and Traditional Ecological Knowledge among the Kuta Indigenous People in Ciamis, West Java - Nurdin, Ahmad Ali; Jamaludin, Adon Nasrullah (Journal of Education Culture and Society, 2024)
Aim. The purpose of this article is to examine the traditional ecological knowledge (environment) of the Kuta indigenous people in Ciamis, West Java. Nature, for them, is an inseparable part and a source of life. They are meticulous and maintain to remain sustainable.Method. This paper's depiction of Kuta village is more of an ethnographic framework. The paper tries to answer whether the ecological knowledge of the Kuta indigenous people is built from their religious awareness (belief system) or not.Results. The results show a relationship between belief systems and traditional ecological knowledge. The Kuta people’s worldview about their natural surroundings is holistic-ecocentric. Their view is based on a belief system that constructs cultural ethics about their environment.Conclusion. The concept of the unity of humans and nature, which is part of their belief system, results in an intersubjective relationship in which all subjects in the universe are not related in a hierarchical context but are equal and mutually exclusive. They respect, care for, influence, share, and need one another.